Comparative quantification of Leishmania infantum in experimental phlebotomine sand fly infections using kDNA and single-copy Meta-1 gene qPCR assays - Porcelli, Stefania; Prudhomme, Jorian; Sádlová, Jovana; Bečvářová, Barbora; Volf, Petr; Depaquit, Jérôme; Robert-Gangneux, Florence (Parasites & vectors, 2026)
BACKGROUND: Leishmaniasis is a parasitic disease transmitted by female sand flies and caused by protozoan parasites of the genus Leishmania. Accurate quantification of parasite load within vectors is essential for understanding transmission dynamics and vector competence. This study compares two quantitative polymerase chain reaction (qPCR) methods for detecting and quantifying Leishmania infantum in three experimentally infected sand fly species (Phlebotomus perniciosus, Phlebotomus argentipes, and Phlebotomus orientalis). METHODS: One method targets kinetoplast minicircle DNA, which offers high sensitivity but limited quantitative precision, while the other targets the single-copy Meta-1 gene, providing more precise quantification but reduced sensitivity in low-level infections. RESULTS: A positive correlation between the two molecular markers supports a combined approach to maximize both sensitivity and accuracy in surveillance and transmission studies. Following this methodological comparison, significant differences were observed in parasite proliferation among sand fly species and L. infantum strains, with Ph. orientalis confirmed as a highly competent vector for Leishmania donovani complex. CONCLUSIONS: Together, these findings highlight that combining high-sensitivity (kinetoplast DNA [kDNA]) and single-copy (Meta-1) targets enables both accurate and sensitive quantification of Leishmania infections in sand flies, improving the assessment of parasite-vector interactions.
Keywords: Leishmaniasis, Visceral; Meta-1 gene; hmyz - vektory; kinetoplastová DNA; Real-Time Polymerase Chain Reaction; Parasite quantification; leishmanióza viscerální; DNA, Kinetoplast; Leishmania infantum; Sensitivity and Specificity; Sand fly vectors; kvantitativní polymerázová řetězová reakce; ženské pohlaví; kDNA; qPCR; Insect Vectors; Phlebotomus; senzitivita a specificita; Animals; zvířata; Female